A semiclassical molecular dynamics of the photochromic ring-opening reaction of spiropyran - Zhai, Gao-Hong; Yang, Pei; Wu, Shao-Mei; Lei, Yi-Bo; Dou, Yu-Sheng (Chinese chemical letters, 2014)
The photochromic ring-opening reaction of spiropyran（SP） has been investigated by a realistic semiclassical dynamics simulation,accompanied by SA3-CASSCF（12 10）/MS-CASPT2 potential energy curves（PECs） of S0–S2.The main simulation results show the dominate pathway corresponds to the ringopening process of trans-SP to form the most stable merocyanine（MC） product.These findings provide more important complementarity for interpreting experimental observations.